Selective propagation of functional mitochondrial DNA during oogenesis restricts the transmission of a deleterious mitochondrial variant. - Hill, J.H.; Chen, Z.; Xu, H. (Nature Genetics, 2014)
Although mitochondrial DNA (mtDNA) is prone to mutation and few mtDNA repair mechanisms exist, crippling mitochondrial mutations are exceedingly rare. Recent studies have demonstrated strong purifying selection in the mouse female germline. However, the mechanisms underlying positive selection of healthy mitochondria remain to be elucidated. We visualized mtDNA replication during Drosophila melanogaster oogenesis, finding that mtDNA replication commenced before oocyte determination during the late germarium stage and was dependent on mitochondrial fitness. We isolated a temperature-sensitive lethal mtDNA allele, mt:CoI(T300I), which resulted in reduced mtDNA replication in the germarium at the restrictive temperature. Additionally, the frequency of the mt:CoI(T300I) allele in heteroplasmic flies was decreased, both during oogenesis and over multiple generations, at the restrictive temperature. Furthermore, we determined that selection against mt:CoI(T300I) overlaps with the timing of selective replication of mtDNA in the germarium. These findings establish a previously uncharacterized developmental mechanism for the selective amplification of wild-type mtDNA, which may be evolutionarily conserved to limit the transmission of deleterious mutations.